Optimization of cultivation medium for levan production using bacillus subtilis in semi-industrial scale - A. Hamid, Khairedza Rahmi (2015)
Levan is extracellular polysaccharides of fructose, and it can be found in plants and microbial products. Recent studies of levan showing characteristics as antitumor, antioxidants, antiviral, therapeutic effects and anticancer agents with fibrinolytic action and were produced from various types of microorganisms. This study focused on medium optimization study of B. subtilis in the shake flask levels on the cell growth and levan production. The effects of bioprocessing parameters was also studied in the semi-industrial scale 16-L bioreactor. Recent studies reported that the highest amounts of levans are produced from the medium with commercial sucrose, with minor quantity of alcohol precipitate. The un-optimized medium yielded the cell mass production of 1.95 g L-1 and 13.5 g L-1 of levan from the shake flasks studies. Then, the cell mass increased to 2.26 g L-1 and the production of levan also increased to 22.1 g L-1 and 21.8 g L-1, respectively after medium optimization using OFAT method and statistical approach. Thus, showed that there was 38.07% increment in levan produced from statistical optimized medium compared to un-optimized medium. Batch cultivations in 16-L stirred tank bioreactors were carried out under un-controlled pH and controlled pH condition by using statistically optimized production medium generated from statistical tool. The new formulation was composed of (g L-1): sucrose, 130.0, yeast extract, 6.3, K2HPO4, 5.0, and MgSO4.7H2O, 0.2. The result showed that bioreactor under uncontrolled pH was favorable compared to controlled pH condition in obtaining the highest amount of cell mass and levan production. From the cultivation under un-controlled pH in the 16-L bioreactor showed high cell mass production of 5.06 g L-1 and 26.65 g L-1 of levan production was produced. This was almost 49.34 % higher than those obtained in shake flask cultivation. However the yield of levan per cell mass was 5.64 g L-1 compared to 11.54 g L-1 from bioreactor with controlled pH due to the low cell mass production. In conclusion, this study proposed a reliable industrial production medium and an effective cultivation strategy for the cell mass and levan production in semi industrial scale.